(untitled) - Moaveni, Saeed (Pacific Grove, CA, 2002)
This book introduces students to basic study skills while also introducing the engineering discipline in the early chapters. Having thoroughly prepared students, the author then introduces basic principles, physical laws, engineering materials, computer tools, and engineering standards and codes at a basic level so students comprehend the importance of these topics. The book features examples from everyday situations, providing students with a meaningful context in which to learn hard-to-grasp topics. Examples of how the skills being learned are applied to different fields of engineering are supported by the opportunity to apply these skills in hands-on exercises. Throughout the text, Moaveni emphasizes strategies for solving engineering problems as well as the importance of communication skills in terms of writing technical reports or memos, and giving oral presentations.
Keywords: Engineering; Kỹ thuật